Biomechanics of Gait during Pregnancy. (21st December 2014) - Branco, Marco; Santos-Rocha, Rita; Vieira, Filomena
Abstract : Introduction . During pregnancy women experience several changes in the body's physiology, morphology, and hormonal system. These changes may affect the balance and body stability and can cause discomfort and pain. The adaptations of the musculoskeletal system due to morphological changes during pregnancy are not fully understood. Few studies clarify the biomechanical changes of gait that occur during pregnancy and in postpartum period. Purposes . The purpose of this review was to analyze the available evidence on the biomechanical adaptations of gait that occur throughout pregnancy and in postpartum period, specifically with regard to the temporal, spatial, kinematic, and kinetic parameters of gait. Methods . Three databases were searched and 9 studies with a follow-up design were retrieved for analysis. Results . Most studies performed temporal, spatial, and kinematic analysis. Only three studies performed kinetic analysis. Conclusion . The adaptation strategies to the anatomical and physiological changes throughout pregnancy are still unclear, particularly in a longitudinal perspective and regarding kinetic parameters.